GSH-conjugation Reduces PGV-1 Cytotoxicity and Its Ability in Downregulating N-Myc, β-catenin, and p62 Protein in Huh-6 Cells - Rohmad Yudi Utomo; Edy Meiyanto; Ratna Asmah Susidarti (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Pentagamuvone-1 (PGV-1), a synthetic curcumin analogue, exhibits potent anticancer activity against Hepatocellular Carcinoma (HCC) by disrupting cell cycle regulation and downregulating key oncogenes such as N-Myc. Numerous studies have examined the role of glutathione (GSH) conjugation in modulating the anticancer properties of curcumin and its analogues. In contrast, the impact of PGV-1 metabolism, particularly GSH conjugation, and its implications for anticancer efficacy have not yet been elucidated. This study was performed to prepare GSH-conjugated PGV-1 (PGV-1-(GSH)2) as the model of PGV-1 metabolite and evaluate its potential distinct cytotoxicity on Huh-6 cells.METHODS: PGV-1 was synthesized via an acid-catalyzed reaction between 4-hydroxy-3,5-dimethylbenzaldehyde and cyclopentanone while PGV-1-(GSH)2 was obtained through reflux at 70oC for 2 hours. The cytotoxic effects of PGV-1 and PGV-1-(GSH)2 on Huh-6 and JHH4, two HCC cells, were assessed using a cell counting kit-8 (CCK-8) assay, while immunoblotting was performed to evaluate their impact on N-Myc and its downstream protein such as β-catenin, and p62.RESULTS: PGV-1-(GSH)2 was prepared through GSH conjugation of PGV-1 in orange color solution, as confirmed by Electrospray Ionization Mass Spectrometry (ESI-MS), Fourier Transform Infrared Spectroscopy (FT-IR), and Nuclear Magnetic Resonance (NMR) analysis. Cytotoxicity assays revealed that PGV-1-(GSH)2 exhibited less potent anticancer activity against HCC cells than PGV-1. GSH conjugation also decreased the ability of PGV-1 in downregulating the N-Myc, β-catenin, and p62 protein level.CONCLUSION: The prepared PGV-1-(GSH)2 reduces the cytotoxicity of PGV-1 and its ability on downregulating N-Myc, β-catenin, and p62 in Huh-6 cells. These findings highlight the need for further exploration about the study of PGV-1 metabolism which could affect the anticancer efficacy against HCC.KEYWORDS: curcumin, PGV-1, GSH, HCC, N-Myc